Pendampingan Penyusunan Purana Banten di Desa Adat Tegaltamu, Desa Batubulan, Kecamatan Sukawati, Kabupaten Gianyar - I Wayan Suwadnyana; Saskara, I Putu Adi; I Nyoman Bontot; I Made Gde Puasa; Ida Ayu Diah Larashanti (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Hinduism is a religion that is full of holidays or ceremonies. Its implementation also often uses offerings or what can be called offerings. Banten can also be interpreted as a guardian. The word wali means representative. Banten in a ceremony is used as a representative to relate to the worshiped or glorified. In addition, the word wali means return. This understanding indicates that offerings are meant to be offered again, which in the beginning all of the offerings came from or were sourced from the creations of Sang Hyang Widhi Wasa. The purpose of this re-offering is to create a balance between God / Ida Sang Hyang Widhi Wasa who has created, and humans as His creatures who receive and enjoy the most, so that they can be sustainable throughout time. Especially in the Tegaltamu Traditional Village, in carrying out the yadnya ceremony using banten so far it has only followed the existing culture and traditions, so that what has become a tradition will be followed and done without knowing whether it is right or wrong. The problem is that in the Tegaltamu Traditional Village, along with the development of the demands of the times that limit time and increase the busyness of the community in terms of earning a living and activities outside the custom, of course they are not easy to carry out the tradition to the fullest, so it is necessary to prepare a basic guideline for community members that is adapted to the needs of the community. current developments, so that community members can adjust their yadnya according to their situation and condition and get certainty about the yadnya ceremony that has been carried out. For this reason, it is necessary to provide assistance in the preparation of the Purana offerings in the Tegaltamu Traditional Village by a team of companions who are members of community service for the Penerangan Agama Hindu Information Study Program I Gusti Bagus Sugriwa Denpasar. There are several stages of mentoring that are passed to produce a Purana Banten. Some of these stages are the assessment stage, socialization and material delivery, field surveys, interviews, focus group discussions, data sorting and the last is the compilation of the results of service activities. Data triangulation method was used during community service activities which included material exposure, discussion, observation, group sharing, data research, book preparation, revision and editing to produce output in the form of printing a book entitled “Purana Banten Pura Dalem Desa Adat Tegaltamu and Purana Banten Pura Desa Desa Adat Tegaltamu”.